Ewolucja węgierskiego modelu zarządzania sądownictwem i samorządu sędziowskiego na Węgrzech w latach 1989–2019 - Grabowski, Radosław; Halász, Ivan (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The Hungarian constitutional system after 1989 was initially subject to evolutionary changes. The previously binding constitution was only amended, although in most countries of the region the new constitutions created new system concepts. This also concerned the organisation of the judiciary, which in Hungary for a long time remained under the influence of the doctrine formed in the time of the socialist state. Significant corrections in this respect did not take place until 1997, but the solutions and institutions created at that time — including judicial self-government — survived for only slightly more than a decade. The political parties that came to power in 2010 adopted a new Basic Law and made far-reaching transformations in the field of symbolism, constitutional principles and the system of constitutional organs. Both the scope of the changes and the way they were carried out provoked resistance from various environments, including judges, whose influence on the organisation of the judiciary and its functioning was significantly reduced. The dispute that occurred was the subject of debate throughout Europe, and the institutions of the Council of Europe and the European Union were involved in resolving it.
Keywords: Hungary; organisation of the judiciary; judicial self-government; constitution